Penggunaan Media “Aprori” Berbasis Diferensiasi untuk Meningkatkan Kreativitas dan Kebhinnekaan Global Siswa - Rini Susdamayanti (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
Creativity and insight into global diversity are two important aspects of education. Creativity produces new, innovative and unique things in solving problems. Diversity insight refers to a deep understanding and tolerance of various existing cultures. These two aspects are still low, especially for class V students at SDN Lomaer 1. This can be seen from the students’ low understanding of the culture in their region, as well as their lack of motivation to study regional culture. This condition is caused by the absence of media and learning models that are able to accommodate the heterogeneous learning needs of students. Therefore, a solution is needed through the use of Apriori media based on product differentiation. This Aprori research uses the research and development (R&D) method with the ADDIE model design, namely, analysis, design, development, implementation and evaluation. Data was collected through observation techniques and learning outcomes tests, analyzed descriptively-qualitatively. The results of the research show that by using media (1) students' creativity in completing dance property projects in the form of masks increased from 69.3% to 82.5% and (2) students' classical insight into global diversity increased from 84.75% to 95%. It can be concluded that the use of Apriori media based on product differentiation can increase the creativity and insight into global diversity of class V students at SDN Lomaer 1.